Combined thoracic segmental spinal anesthesia and erector spinae plane block in high-risk patients undergoing thoracoscopic surgery: A case series - GS Karthik; Mahesh Chandra; R Sudheer; A H Shwetha (Saudi Journal of Anaesthesia)
Thoracoscopic surgery in high-risk patients with severe respiratory disease is associated with a high morbidity and mortality rate. Though general anesthesia is the first-line anesthetic strategy for thoracoscopic surgeries, it poses a significant risk. When the hazards of general anesthesia outweigh the benefits of the procedure, there is a moral quandary over whether thoracoscopy should still be the option for patients with severe respiratory disorders. Thoracic segmental spinal anesthesia in combination with erector spinae block may emerge as an excellent alternative to general anesthesia in terms of analgesic efficacy, patient recovery profile, and minimal complication rates if administered by experienced hands. Unfortunately, there is paucity of literature exploring the impact of regional techniques and their outcomes on these patients. In this case series, we aim to emphasize that combined thoracic segmental spinal anesthesia and erector spinae plane block are a safe and effective alternative to general anesthesia in thoracoscopic surgeries.